2017
DOI: 10.3892/ol.2017.6217
|View full text |Cite
|
Sign up to set email alerts
|

Sodium butyrate enhances the growth inhibitory effect of sunitinib in human renal cell carcinoma cells

Abstract: Abstract. Sunitinib (SU) is a small molecule that inhibits the receptor tyrosine kinase (RTK) signaling pathway, and has been clinically used to treat advanced renal cell carcinoma (RCC). However, SU is not always effective as RCC is a highly chemoresistant type of cancer. One of the factors that confer chemoresistance to RCC is a hypoxic condition. Lack of oxygen activates hypoxia-inducible factor (HIF) protein, which is followed by the upregulation of growth factors, including vascular endothelial growth fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…HDACIs exert antitumor activity by inducing cell cycle arrest, apoptosis, and autophagy and inhibiting angiogenesis, the activation of oxidative stress, and mitotic cell death [9,34] . A number of preclinical studies have confirmed that HDACIs alone or in combination with other drugs exert strong anti-RCC effects [35–39] . HDACIs alone inhibit the growth of RCC cells by increasing the acetylation of histone 3 and tubulin, whereas the combination of HDACIs with sorafenib [a small molecular multikinase inhibitor of vascular endothelial growth factor receptor (VEGFR)] reduces cell viability by activating caspases and decreasing the levels of myeloid leukemia cell differentiation protein (MCL1), phospho-extracellular signal-regulated kinase (ERK), and secreted VEGF [35] .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…HDACIs exert antitumor activity by inducing cell cycle arrest, apoptosis, and autophagy and inhibiting angiogenesis, the activation of oxidative stress, and mitotic cell death [9,34] . A number of preclinical studies have confirmed that HDACIs alone or in combination with other drugs exert strong anti-RCC effects [35–39] . HDACIs alone inhibit the growth of RCC cells by increasing the acetylation of histone 3 and tubulin, whereas the combination of HDACIs with sorafenib [a small molecular multikinase inhibitor of vascular endothelial growth factor receptor (VEGFR)] reduces cell viability by activating caspases and decreasing the levels of myeloid leukemia cell differentiation protein (MCL1), phospho-extracellular signal-regulated kinase (ERK), and secreted VEGF [35] .…”
Section: Discussionmentioning
confidence: 99%
“…HDACIs or 5-aza-2’-deoxycytidine (5-Aza) (an inhibitor of DNA methyltransferases) alone suppresses the proliferation of RCC cell lines by promoting apoptosis and inducing cell cycle arrest, and the 2 drugs administered in combination exert a synergistic antiproliferation effect [36] . In other studies, HDACIs combined with programmed cell death protein 1 (PD-1) inhibitors, receptor tyrosine kinase (RTK) inhibitors, or 5-fluorouracil significantly restrained RCC cell growth, and the effect of the combination was significantly better than that of HDACIs alone [37–39] . However, due to the different expression of HDACs in tumors and the resistance of tumors to HDACIs, the therapeutic effect of pan-HDACIs on solid tumors is limited in clinical practice [16,18,40] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Butyrate is a natural nutrient found in certain foods, such as butter and milk, but most of the butyrate in the human body comes from gut microbiota fermentation of undigested carbohydrates 23 . Butyrate is usually administered as sodium butyrate (NaB) and exhibits various physiological roles, antitumor effects, inflammation, and glucose regulation 24–28 . The metabolic benefits of NaB have been identified in several different metabolic diseases, such as T2DM and CVD.…”
Section: Introductionmentioning
confidence: 99%
“…23 Butyrate is usually administered as sodium butyrate (NaB) and exhibits various physiological roles, antitumor effects, inflammation, and glucose regulation. [24][25][26][27][28] The metabolic benefits of NaB have been identified in several different metabolic diseases, such as T2DM and CVD. In a high-fat diet (HFD)induced T2DM model, cardiac function and metabolic dysfunction were ameliorated by NaB.…”
mentioning
confidence: 99%